Escherichia coli Isolated from Urinary Tract Infections of Lebanese Patients between 2005 and 2012: Epidemiology and Profiles of Resistance - Daoud, Ziad; Salem Sokhn, Elie; Masri, Khalil; Cheaito, Katia; Haidar-Ahmad, Nathaline; Matar, Ghassan M.; Doron, Shira (Frontiers in Medicine, 2015)
The early treatment of urinary tract infections is directly related to decrease in morbidity, which makes the empirical treatment of great importance. Recently, beta lactamases of several types have emerged as significant mechanisms of resistance in Gram negative bacilli, especially Escherichia coli. Our aim was to study the urinary E.coli isolated from Lebanese patients and to characterize their mechanisms of resistance. The study analyzed data between 2005 and 2012 of urinary tract infections caused by E.coli. The mechanisms of resistance were characterized by phenotypic and genotypic methods and the Pulsed Field Gel Electrophoresis was used to determine the different bacterial clusters. As expected, the highest incidence was observed with E. coli (60.53 to 73.98%) followed by K pneumoniae (5.32 to 8.33%). ICU isolates were constantly associated with the lowest rates of susceptibility to extended spectrum cephalosporins, ciprofloxacin, as well as most of the tested antibiotics. A 100% occurrence of CTX-M in ESBL producing isolates was recorded, followed by TEM, SHV, and OXA. In addition, 15.9% harbored 4 different ESBL enzymes and only 13 isolates (14.8%) harbored only one enzyme (CTX-M). Over the years, the simultaneous susceptibility of E. coli to ceftazidime and ciprofloxacin decreased from 62.5% in 2006 to 48.7% in 2012. PFGE results demonstrated that 10 clusters were 32 generated, denoting diversity among detected isolates. Understanding the epidemiology of resistance is 33 instrumental for the implementation of recommendations for the management of antimicrobials, infection 34 control measures, as well as active surveillance and antimicrobial stewardship.